Indonesian Houses : Volume 2: Survey of Vernacular Architecture in Western Indonesia. - Schefold, R. (Brill, 2008)
This collection aims to attract attention to the admirable achievements of indigenous builders in Indonesia and to contribute to a broader sense of commitment to the endangered architectural heritage in the region. It presents the second part of the results of a research project on vernacular architecture in western Indonesia, sponsored by the Royal Netherlands Academy of Sciences. The volume is intended to provide an introduction to all relevant vernacular architectural traditions and developments in western Indonesia. The 21 contributions, all written by researchers with long first-hand experience in the area they are dealing with, are arranged according to the location of the ethnic groups from west to east--from Aceh to Western Java. Each contributor was asked to enrich the architectural description with a self-chosen particular topic illustrating social, ideological and environmental peculiarities of the field situation. The book takes account of the rich diversity of the various contexts and artistic elaborations that developed in the region. The first collection of essays, Indonesian houses, Volume 1: Tradition and transformation in vernacular architecture , was published as nr. 207 of the Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde (Leiden, 2003). It focussed on case studies demonstrating how a common architectural heritage has been affected by historical changes, giving shape to a multiplicity of local developments and adaptations both in their material aspects and in their functions as objects of social value and meaning.